Tourist Satisfaction: The Role of Tour Guide Competence in Destination Management - Kurniawan, Krisanti; Kusumaningsih, Riski Putri; Hengky, SH (Finance : International Journal of Management Finance, 2025)
In the context of tourism destination management, this study examines the relationship between tour guide competence and tourist satisfaction. Tourism publications often provide important input for tourists, particularly regarding their travel experiences or stories. This survey data involved a sample of 100 domestic and international tourists, predominantly respondents of productive age, who were national tourists. The data tabulation used in this study using SPSS v29 was used for descriptive data analysis, reliability testing, and regression analysis. The findings indicate that competency dimensions—communication competence, cultural knowledge, problem-solving skills, and professionalism—play a significant role in increasing tourist satisfaction. The implications of this research are useful for tourism destination managers and policymakers. A limitation of this study is that it does not yet address internal and external motivations and/or tourist objectives.